Z zagadnień ontologicznych informatyki - Bondecka-Krzykowska, Izabela (Wydawnictwo Naukowe UAM, 2016)
From ontological issues of computer science takes a look at this field through the eye of the philosopher, and contains an analysis of selected ontological issues related to computer science. It also constitutes an attempt to define computer science as a scientific discipline through the prism of the objects it researches. The book presents fundamental problems of philosophy related to the following terms: the computer, computer programmes, information and virtual reality. It analyses their nature, mutual relations and the attempts made to create an ontology for computers, programmes, information and virtual reality as objects of enquiry for computer science. The influence of emerging concepts related to computer science for particular classic concepts and ontological questions is also described.
From ontological issues of computer science
Książka zawiera analizę wybranych zagadnień ontologicznych związanych z informatyką. Jest ona próbą odpowiedzi na pytanie, jakie obiekty badają informatycy oraz jaki jest ich status ontologiczny. Monografia zawiera szczegółową analizę spotykanych w literaturze poglądów dotyczących tej kwestii oraz propozycje własne autorki. W kolejnych rozdziałach poddano analizie komputery, programy komputerowe, informację oraz wirtualną rzeczywistość jako obiekty informatyki.
Keywords: filozofia informatyki; ontologia; komputer; program komputerowy; informacja; wirtualna rzeczywistość